(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The effectiveness of higher education services plays a crucial role in the development of society and the economy, influencing workforce quality and the nation’s competitive edge. As demands for better educational outcomes and improved institutional performance rise, it becomes essential to explore strategies for enhancing the organizational and economic mechanisms of higher education. This article analyzes the existing practices in higher education services, identifies inefficiencies, and proposes improvements in the organizational and economic mechanisms necessary to increase their effectiveness.